A Method to Evaluate Business Process Conceptual Models : A Study Case - Salgado, Carlos Humberto (2013)
The business process conceptual models present a global vision of the organization. It allows to better understand the enterprise's dynamic and its internal relations and with its environment. The business modeling is the main technique for aligning the development with the enterprise goals. In this context, the models have a fundamental role in the business process specification. For this reason, it is important their quality for helping to improve the performance and organization evolution. This characteristic is relevant in order to avoid that they be a risk factor. Taking into account the characteristics before mentioned, a method to evaluate business process conceptual models is proposed. The goal is to provide to the organization an approach to help them to study the business process quality. This study is carried out taking as point of view both their understandably and their adaptability to the changes.